Programa educativo lúcido dinámico para estimular la motricidad fina en niños/as de 4 años de la I.E.I N°288 – Rioja - Barboza Marín, Rocio Elizabeth (2015)
The purpose of this research was to develop dynamic to stimulate fine motor skills in children 4 years of lnitial Educational lnstitution of Rioja playful educational program. To meet the objectives, it was based on the theories of Vygotsky's sociocultural learning; psicogenética Piaget; Henry Wallon tone and body analysis of the relationship of André Lapierrey where the study variables were conceptualized. Such theoretical framework allowed to pose the following hypothesis: lf we apply the dynamic playful educational program, then significantly stimulate fine motor skills in children 4 years of lnitial Educational lnstitution No. 288 - Rioja. The research design was pretest and post test with one group, which belongs to pre experimental design. The sample consisted of 14 children from 4 years of lnitial Educational lnstitution No. 288 of Rioja. This group was administered a testobservation guide with 21 indicators with which fine motor coordination was evaluated eye - hand, socio-emotional, cognitive and physical, to playful dynamic educational program was applied structured level planning (lnitial diagnosis fine motor), organization (structure of dynamic gamas), running (04 workshops and 09 games) and evaluation (befare, during and after the process). In analyzing the results of the investigation we found that the application of dynamic playful educational program, significantly stimulated the fine motor skills in children 4 years of initial school No. 288- Rioja shown by the averages obtained in the pretest ( X= 14,00) and post (X= 17,05), reaching the category of Fine Motor Regular (MFR), obtaining a obtaining a calculated value te= -2,713and a tabular valuet1 = -1,729, with a significance level of 5%.